Energy efficiency retrofit at Sultanah Zanariah Library, Universiti Teknologi Malaysia - Universiti Teknologi Malaysia. Institut Sultan Iskandar; ENCEFF Sdn. Bhd (Skudai : Universiti Teknologi Malaysia, 2001)
18